Efficiency of fish-friendly intakes, bypasses associated with low bar-spacing trashracks, for downstream migration of Atlantic salmon smolts - Sagnes, Pierre; Tomanova, Sylvie; Courret, Dominique; Alric, Alain; De-Oliveira, Eric; Tétard, Stéphane (2016)
Lessons learned about the efficiency of fish-friendly water intakes at 4 power plants in France.